Evaluation of Pongamia Oil Soap Against Major - Anu Thomas (Depatment of Agricultual Entomology, College of Agriculture, 2019)
The proposed study entitled, Evaluation of pongamia oil soap against major pests of okra, Abelmoschus esculentus (L). Moench was aimed at evaluating the efficacy of a new product made of pongamia oil - pongamia oil soap at different concentrations in combating the major pests of okra viz., shoot and fruit borer, leaf roller and leaf hopper. Laboratory bioassay of pongamia oil soap was carried out in the Department of Agricultural Entomology, College of Agriculture, Padannakkad, during 2018-19 to evaluate the feeding deterrency and growth retardation properties of pongamia oil soap against fourth instar and first instar larvae of bhindi leaf roller, Sylepta derogata respectively and its insecticidal property or repellent property on bhendi leaf hopper, Amrasca biguttula biguttula. The test organisms were exposed to six treatments viz., T1: Pongamia oil soap 0.6%; T2: Pongamia oil soap 1%; T3: Pongamia oil soap 2%; T4: Neem oil soap 0.6%; T5: Soap solution 0.5%; T6: control with three replications under completely randomised design (CRD). Among the different treatments, pongamia oil 2 per cent showed the maximum antifeedent activity on fourth instar larvae and maximum growth retardation activity on first instar larvae of S. derogata. Spraying of pongamia oil soap 2 per cent showed 100 per cent mortality of leaf hoppers by 16 h after the treatment. But neem oil soap 0.6 per cent and pongamia oil soap 0.6 per cent took 24 h to attain 100 per cent mortality. Field efficacy of pongamia oil soap was evaluated by randomised block design (RBD) with seven treatments and four replications on okra variety ‘Arka Anamika’ during rabi and summer seasons at the Instructional farm in College of Agriculture, Padannakkad. The treatments applied were: T1: Pongamia oil soap 0.6%; T2: Pongamia oil soap 1%; T3: Pongamia oil soap 2%; T4: Neem oil soap 0.6%; T5: Soap solution 0.5%; T6: Quinalphos 0.05% - (Standard check); T7: Control. All treatments were applied once at vegetative stage and twice during reproductive stage. Observations were taken one day prior to treatment and 1, 3, 5, 7 and 14 days after treatment (DAT) for sucking pests. Damage symptoms caused by lepidopteran pests were observed one day prior to and 7 and 14 DAT. After three sprays during the rabi season pongamia oil soap 2 per cent was superior among botanicals in reducing the leaf hopper population significantly as compared to that of control. The effectiveness against leaf hopper lasted up to seven days after treatment. By the end of the rabi season pongamia oil 2 per cent showed significant reduction in damaged leaves as compared to other botanicals whereas the damage per cent was significantly increased in control and soap solution 0.5 per cent. Damage caused by leaf roller was cut down by the treatment of pongamia oil soap 2 per cent for seven days due to its antifeedent, repellent and growth retardation activity. Mean percentage of shoots and fruits infested by okra shoot and fruit borer Earias vitella and fruit borer Helicoverpa armigera during rabi and summer season was observed lowest in pongamia oil 2 per cent among botanicals. Reduction in mean per cent of fruit and shoot damage by pongamia oil soap may be due to the feeding deterrency of pongamia oil which remained effective for seven days. However all the treatments were effective in reducing the pest infestation except soap solution 0.5 per cent. Effectiveness of pongamia oil soap was observed to decline after seven days after spray application. Higher concentration of the soap gave better results as compared to that of lower concentrations. Pongamia oil soap 2 per cent exhibited increased fruit yield and marketable yield as compared to that of control due to lower incidence of pests during both the seasons. Economics of pongamia oil soap 2 per cent in turns of cost benefit ratio was also high as compared to control in both rabi and summer seasons, making it an effective component in IPM programmes and organic farming.